The impact of meditation aided by VR technology as an emerging therapeutic to ease cancer related anxiety, stress, and fatigue - Franklin, D. Michael; Silvestro, Charles; Carrillo, Robert A.; Yang, Yewon; Annadurai, Dharani; Ganesan, Sangavai; Vasantham, Divya Sai Jyothi; Mettu, Soujanya; Patel, Mehal; Patil, Manasi S.; Akurathi, Nandini Devi (Frontiers in Virtual Reality, 2023)
Patients diagnosed with cancer experience a high degree of stress as well as side effects from treatments that can greatly impact their quality of life. Many patients experience long-term side effects such as pain, fatigue, anxiety, depression, and cognitive dysfunction. Several studies have reported that the use of virtual reality (VR) interventions show substantial benefits in reducing symptoms of anxiety, depression, pain, and cognitive functions in cancer patients undergoing therapy. In this study we analyzed the acceptability, feasibility, and tolerance of PNI Thrive, a 10-minute VR guided meditation application, as an adjuvant digital therapeutic aid for cancer patients in a clinical setting. Patients diagnosed with various cancers, and at different stages of therapy, participated in this study. Our data suggests that the adjuvant VR treatment was successful in making patients feel calmer, more relaxed, refreshed, and more empowered. We propose that routine exposure of patients to VR interventions will help improve their response to anti-cancer therapies and quality of life.